Rational Design of Titanium Carbide MXene Electrode Architectures for Hybrid Capacitive Deionization. Issue 3 (10th August 2020) - Buczek, Samantha; Barsoum, Michael L.; Uzun, Simge; Kurra, Narendra; Andris, Ryan; Pomerantseva, Ekaterina; Mahmoud, Khaled A.; Gogotsi, Yury; Agnese, Yohan Dall'
Abstract : Intercalation redox materials have shown great promise for efficient water desalination due to available faradaic gallery sites. Symmetric capacitive deionization (CDI) cells previously demonstrated using MXenes were often limited in their salt adsorption capacity (SAC) and voltage window of operation. In this study, current collector‐ and binder‐free Ti3 C2 T x MXene electrode architectures are designed with porous carbon as the positive electrode to demonstrate hybrid CDI (HCDI) operation. Furthermore, MXene current collectors are fabricated by employing a scalable doctor blade coating technique and subsequently spray coating a layer of a small flake MXene dispersion. Hydrophilic redox‐active galleries of MXenes are capable of intercalating a variety of aqueous cations including Na +, K +, and Mg 2+ ions, showing volumetric capacitances up to 250 F cm ‐3 . As a result, a salt removal capacity of 39 mg g ‐1 with decent cycling stability is achieved. This study opens new avenues for developing freestanding, binder‐ and additive‐free MXene electrodes for HCDI applications. Abstract : Efficient hybrid capacitive deionization employing faradaic MXene electrode combined with porous carbon electrode